Enhanced Bandwidth Tunability in Thermally Controlled Multi-Pitch Contra-Directional Couplers - Lorenzo Tunesi; Vittorio Curri; Andrea Carena; Paolo Bardella (IEEE Photonics Journal)
Grating-Assisted Contra Directional Couplers (GACDCs) are versatile photonic devices which can implement free-spectral-range free add-drop flat-top responses, making them interesting solutions for Wavelength Division Multiplexing (WDM) systems and many other applications requiring spectral shaping. Their bandwidth can be dynamically changed through thermal means, granting an additional degree of freedom in their design and application. Design techniques involving the periodicity of the gratings (pitch chirping) can enhance the effect of this dynamic control, leading to wider bandwidth tunability in terms of both central channel wavelength and passband width, while leaving the control mechanism and power unchanged. In this work, we investigate the limits of these effects, highlighting the advantages through simulation of both the optical response and the thermal control.